PELATIHAN PENGGUNAAN INTERNET SEHAT UNTUK ANAK USIA DINI - Sri Ratna Wulan; Asri Maspupah; Cholid Fauzi; Ani Rahmani; Akhmad Bakhrun; Joe Lian Min (Universitas Mataram, 2023)
From an early age, children already use a gadget for entertainment. For example, they use it for watching an animation or playing games. However, internet without supervision will harm children's development and increase potential dangers such as sexual crimes, cyberbullying, speech impediments, anti-social, decreased physical health, and easy tantrums. We need awareness of healthy internet use. Meanwhile, kindergarten teachers and parents of students at the Baiturrahman Playgroup Foundation (KB) have limited knowledge of internet use. We held this community service (PkM) to teach the teachers and parents about the importance of healthy internet use, the potential dangers of social media, how to limit the content, and how to protect internet privacy. This training uses lectures, discussions, practice of technical skills, reward for active participants. This community service activities include planning, preparation, implementation, and evaluation. This community service is a success if the participant's knowledge is increased and the level of satisfaction with the implementation of the activity is high. The output consists of profiling the knowledge of the training participants on healthy internet use, training modules, and training evaluation results. We got participant's knowledge and attitude by conducting a survey. The result showed that the participants did not understand the negative impacts of using internet without privacy protection and parental supervision. We also conducted a survey about the satisfaction of the event. It showed that 54.55% of participants experienced increased their knowledge, and 75.61% of participants gave a satisfaction index above 80% (Very Satisfying). With this community service, teachers and parents of students have realized the importance of educating about healthy internet use from an earlier age by providing restriction and supervision through information technology.